Pengembangan Wawasan Kebangsaan Melalui Media Sosial (Studi Kasus Warganet Indonesia dalam Isu yang Mengusik Nasionalisme) - Dewanto Samodro; Jati Satrio; Chairun Nisa Zempi (Universitas Persada Indonesia YAI, 2023)
Indonesian citizens are individuals who actively use social media. A study showed that more than half ofIndonesians used social media. Not infrequently, Indonesian netizens act in response to a number of issuesthat disturb the nation's sense of nationalism. This study uses a qualitative case study method to captured howIndonesian netizens responded to a number of issues that disturb the sense of nationalism, as well as providean illustration that netizens' activities in Indonesia are a potential in developing national insight through socialmedia.